COVID-19 Pandemic on MSMEs in Bandar Lampung - Yuliansyah, Yuliansyah; Listyaningsih, Erna; Sariningsih, Eka; Indriani, Wiewiek (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 2 (2022)DO - 10.24843/JIAB.2022.v17.i02.p07, 2022)
The COVID-19 pandemic has an impact on the global economy, including MSMEs. The purpose of this study was to determine the impact of COVID-19 on the financial performance and labor of MSMEs in the Bandar Lampung banana chip center, as well as the impact of labor on financial performance and labor as an intervening factor. The data collected were analyzed using Partial Least Square. It was found that the COVID-19 pandemic had an impact on financial performance and labor. Additionally, labor had an influence on financial performance. The main strength in this study is the discovery of direct and indirect effects of the COVID-19 pandemic on financial performance, with labor acting as an intervening variable between the COVID-19 pandemic and financial performance. This finding implies that people are used to the new normal life namely by carrying out routine activities while implementing health precautions to avoid the COVID-19 transmission. Keywords : COVID-19 pandemic, the effect of COVID-19 pandemic, MSME